SEISMISITY ANALYSIS OF SHALLOW EARTHQUAKE AT CENTRAL ACEH IN 2010-2018 - Ichsan, Muhammad
Sumatra Island is one of the islands that has high seismic activity because of its location close to the subduction zone between the Indo-Australian and Eurasian plates and the existence of Great Sumatran Fault (GSF). The Aceh segment in the northern part of the Sumatra Fault has a high seismicity. Many earthquakes occurred in the period 2010 to 2018 around the Central Aceh region. In this area there are faults that were active in parallel with the Great Sumatra Fault (GSF). Tectonic earthquakes caused by stress that occurs inside the earth. One of the information that can determine stress is the earthquake's focus mechanism. The purpose of this study was to analyze stress orientation from the focus mechanism data that occurred due to local earthquakes in Central Aceh. This study used 388 events with a depth of < 50 km with a magnitude > 3 Mw recorded by nine seismic stations belonging to BMKG for the period of 2010 to 2018. The initial process carried out was picking the arrival times of P and S waves towards earthquake waveform data. After that, the initial hypocenter determination uses the Hypoellipse program with the principle of the Geiger method. The next step is relocation which applies the double-difference method which results in better relocation results. The relocation resulted in two earthquake clusters associated with the Batee fault and GSF fault along Tangse-Geumpang. The two clusters were studied with a focus mechanism using the moment tensor inversion method. From the results of the focus mechanism obtained data strike, dip, and rake. The data is used as input in the stress inversion process with the Iterative Joint Inversion method to determine the orientation of the main stress and shape ratio. The inversion results produce stress horizontal maximum which is relatively N-W, showing the accumulation of stress from the Indo-Australian plate subduction activity with the Eurasian plate.